Fire cues trigger germination and stimulate seedling growth of grass species from Brazilian savannas. Issue 9 (26th August 2019) - Ramos, Desirée M.; Valls, José F. M.; Borghetti, Fabian; Ooi, Mark K. J.
Abstract : Premise: Although fire cues (high temperatures and smoke) influence seed germination in numerous species from fire‐prone environments, their effects on seed germination of species from neotropical savannas are poorly understood. Methods: We exposed seeds of eight grass species from the Cerrado, the Brazilian savanna to heat‐shock (80°C or 110°C for 5 min) and/or smoke water, and then set them to germinate in light or dark, at either summer (28°C/18°C) or winter (27°C/14°C) temperature regimes in an incubator. In addition, we evaluated the effects of smoke water on seedling root and shoot growth for four of the species. Results: Smoke interacted with the dark treatment to increase germination from 28% to 93% in Aristida recurvata and 77% to 95% in Aristida riparia . Smoke had no effect on germination of either of these species in the light. Heat‐shock alone also promoted seed germination in A . recurvata . For Digitaria lehmanniana, smoke interacted with heat‐shock to improve germination from 5% to 16%. In contrast, the fire treatments did not have any effect on the seed germination of the remaining five species. Smoke water stimulated root growth for A. riparia, A. recurvata, and Ctenium cirrosum but had no effect on their shoot growth. Conclusions: The strong promotive effect of smoke on Aristida germination suggests that these species are fire‐adapted. Aristida species have an active awn system, which facilitates seed burial, and the smoke and dark interaction would ensure buried seeds germinated post‐fire. The species that showed no response to fire cues may either have adapted via alternative strategies or require different concentrations of smoke or levels of heat. This study is one of very few examples showing a positive germination and seedling growth response to smoke for species from neotropical savannas.